Comparative study of frictional forces generated by NiTi archwire deformation in different orthodontic brackets: In vitro evaluation Estudo comparativo da força de atrito produzida pela deformação de arco NiTi em diferentes braquetes ortodônticos: avaliação in vitro - Gilberto Vilanova Queiroz; Rafael Yagüe Ballester; João Batista De Paiva; José Rino Neto; Giselle Mara Galon (Dental Press Editora, 2012)
INTRODUCTION: The purpose of this study was to compare the frictional forces between 0.014-in NiTi wires (Aditek) with 4 mm horizontal deflection and brackets with different archwire ligation systems. METHODS: Four types of self-ligating brackets (Damon MX, Easy Clip, Smart Clip and In-Ovation), a triple bracket (Synergy) and a twin bracket with 8-shaped ligature (Tecnident) were tested. Twin brackets with conventional elastomeric ligatures (Morelli) were used as control group. Tests were repeated 10 times for each bracket/archwire combination. Frictional forces were measured in an Instron universal tensile machine at 3 mm/minute speed and a total displacement of 6 mm. Statistical analysis comprised ANOVA and Dunnett's multiple comparison post hoc test. RESULTS: Deflection-induced frictional (DIF) forces increased in the following order: Synergy, Damon, 8-shaped Ligature, Easy Clip, In-Ovation, Smart-Clip and conventional ligatures. The differences among groups were significant, with the exception of the 8-shaped ligature groups which was equal to the Damon and Easy Clip groups. CONCLUSIONS: Compared to conventional ligatures, all ligation systems tested reduced frictional forces. However, such reduction varied according to the ligation system employed. OBJETIVO: o objetivo desse trabalho foi comparar as forças de atrito entre fios NiTi 0,014" (Aditek) com deformações horizontais de 4mm, e braquetes com diferentes sistemas de ligação dos arcos. MÉTODOS: foram testados 4 tipos de braquetes autoligáveis (Damon MX, Easy Clip, Smart Clip e In-Ovation), um braquete triplo (Synergy) e um braquete gêmeo com amarrilho 8 (Tecnident). Como grupo controle, foi utilizado braquete gêmeo com ligadura elástica convencional (Morelli). Foram executadas 10 repetições em cada combinação arco/braquete. As forças de atrito foram medidas em máquina de tração universal Instron, com velocidade de 3mm/minuto e deslocamento total de 6mm. Para análise estatística, usou-se a ANOVA e o Teste de Comparações Múltiplas de Dunnett. RESULTADOS: as forças de atrito por deformação do fio se mostraram crescentes na seguinte ordem: Synergy, Damon, amarrilho 8, Easy Clip, In-Ovation, Smart-Clip e ligadura convencional. As diferenças entre todos os grupos foram estatisticamente significantes, com exceção do Amarrilho 8 em relação aos grupos Damon e Easy Clip. CONCLUSÃO: em relação à ligadura convencional, todos os sistemas de fechamento das canaletas testados são eficientes em reduzir a força de atrito, porém, tal redução varia significativamente de acordo com o sistema de fechamento da canaleta selecionado.